2019
DOI: 10.3389/fmicb.2019.01261
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-Associated Microbiota in Gastric Cancer Tissues Compared With Non-cancer Tissues

Abstract: The link between microbiota and gastric cancer (GC) has attracted widespread attention. However, the phylogenetic profiles of niche-specific microbiota in the tumor microenvironment is still unclear. Here, mucosa-associated microorganisms from 62 pairs of matched GC tissues and adjacent non-cancerous tissues were characterized by 16S rRNA gene sequencing. Functional profiles of the microbiota were predicted using PICRUSt, and a co-occurrence network was constructed to analyze interactions among gastric microbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
120
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(135 citation statements)
references
References 48 publications
14
120
1
Order By: Relevance
“…Interestingly, richness was signi cantly higher in GC cases in the current study population. A similar nding has been reported in the study compared cancer tissues with non-cancer tissues where there is a high microbial richness in GC tissues [21]. Moreover, we observed that there was a higher Shannon index in the controls than the GC group.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Interestingly, richness was signi cantly higher in GC cases in the current study population. A similar nding has been reported in the study compared cancer tissues with non-cancer tissues where there is a high microbial richness in GC tissues [21]. Moreover, we observed that there was a higher Shannon index in the controls than the GC group.…”
Section: Discussionsupporting
confidence: 90%
“…A study focused on the relationship between gastric dysbiosis and GC development found that there is an increased richness although the Shannon index is lower in the GC group compared to controls which is similar to our ndings [43]. On the contrary, a study conducted on microbiota in gastric mucosa in the GC tissues compared with the non-cancer tissues revealed that there is a signi cantly higher Shannon index in the cancer group compared with the healthy controls [21]. A study reported that 75.86% was captured by the rst two principal coordinates in the PCoA beta diversity plot according to the weighted UniFrac phylogenetic distance measure.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…It is known that microbiota-related analyses are able to give only a short overview owing to differences in mouse and human gastric tract structure and metabolism, among others. The gastric microbiota of GC patients was shown to be enriched in nitrosating bacteria; such nitrate-reducing activity increases the intragastric concentrations of nitrite and N-nitroso compounds, which have been reported to increase the risk of GC development [51,52].…”
Section: Microbiota In Gastric Adenocarcinomamentioning
confidence: 99%
“…Treponema denticola, Streptococcus mitis, Streptococcus anginosus [18] Fusobacterium nucleatum [3] Porphyromonas, Fusobacterium nucleatum [30] Gastric cancer Proteobacteria (Xanthomonadaceae and Enterobacteriaceae, as well as genera such as Citrobacter, Phyllobacterium and Achromobacte), Firmicutes (Lactobacillus, Clostridium), Bacteroidetes, Actinobacteria (Rhodococcus) and Fusobacteria [44,49,50] oral bacteria (Peptostreptococcus, Streptococcus, and Fusobacterium) [52] bacteria harbouring nitrosating enzymes [51,52] Pancreatic cancer…”
Section: Esophagus Cancermentioning
confidence: 99%